Uncommon pathogen: Serious manifestation: A rare case of Achromobacter xylosoxidans septic arthritis in immunocompetetant patient - Kalpana Tikaram Suryavanshi; Sanjay K Lalwani (Wolters Kluwer Medknow Publications, 2015)
Achromobacter xylosoxidans is a rare opportunistic Gram-negative bacilli and rarer etiology of septic arthritis. We present here the first Indian case of septic arthritis due to A. xylosoxidans in 11-month-old male child confirmed by 16S rRNA sequencing. The child was admitted as suspected case of septic arthritis and underwent arthrotomy. Drained pus revealed Gram-negative bacilli, identified as Serratia odorifera by API (bioMérieux, Marcy l'Ιtoile, France), later subjected to VITEK 2 (bioMérieux, Marcy l'Ιtoile, France) identification revealing it to be A. xylosoxidans. It being a rare etiology of septic arthritis confirmation was done with 16S rRNA Sequencing.